Integrating Prophetic Values in Mathematics Learning: Enhancing Connection Abilities and Islamic Character in Middle Schools - Litsa Arfi Hidayati; Kusno Kusno; Md. Mahmudul Alam (Jurnal Pendidikan MIPA, 2026)
Mathematics learning in madrasahs has largely focused on conceptual understanding, while the systematic integration of spiritual values into mathematics instruction remains limited. Consequently, students’ mathematical connection ability (MCA) and Islamic character (IC) are often developed separately rather than through an integrated learning process. This study aimed to develop student worksheets (LKPD) based on a prophetic approach and to examine their validity, practicality, and effectiveness in improving both MCA and IC. The study employed a Research and Development (R&D) design using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The participants were seventh-grade students of a Madrasah Tsanawiyah, involving a limited trial class, an experimental class, and a control class. Data were collected through expert validation sheets, student practicality questionnaires, MCA tests, and IC questionnaires, supported by classroom observations and interviews. Descriptive analysis was used to determine the validity and practicality of the developed LKPD, while inferential analysis was conducted using Multivariate Analysis of Covariance (MANCOVA) with pretest scores as covariates. The results showed that the developed LKPD achieved 85% validity and 90% practicality, indicating that the worksheets were feasible and well accepted in classroom learning. The MANCOVA results further revealed a statistically significant effect of the prophetic-approach-based LKPD on students’ MCA and IC (p < 0.05) after controlling for initial differences. Findings from classroom observations and student reflections also indicated that integrating prophetic values encouraged responsible participation, collaborative engagement, and reflective thinking during learning activities. These results suggest that integrating prophetic principles humanization, transcendence, and liberation into mathematical tasks can support both conceptual understanding and character development within mathematics learning. Overall, the study highlights the potential of value-integrated instructional materials to promote more holistic mathematics learning in madrasah contexts. Keywords: LKPD, prophetic approach, mathematical connection ability, islamic character, madrasah tsanawiyah.